Utilization of reconstituted corn grain silage in supplements for finishing beef cattle on pasture: evaluation of supplement aerobic stability and cattle performance - Saulo Teixeira Rodrigues de Almeida [UNESP] (2024)
Two experiments were conducted aiming to: 1) evaluate the combination of Lactobacillus buchneri + Lactobacillus hilgardii and Lactobacillus buchneri + Lactobacillus plantarum in the ensiling of reconstituted corn grains and their effects on silage fermentation, nutritional value, and aerobic stability of the silage and the supplement made with these silages; 2) to determine the impacts of providing fresh and exposed reconstituted corn grain silage supplements on the intake and performance of pasture-finished Nellore cattle with high supplementation. Experiment one evaluated reconstituted corn grain silages non-inoculated and inoculated with L. buchneri + L. hilgardii both in concentration of 1.5 x105 cfu/g and L. buchneri + L. plantarum at 2 x105 cfu/g and 1 x105 cfu/g respectively, stored for 60 days and supplements for beef cattle using these silages. Inoculated silages presented a higher number of lactic acid bacteria, pH and aerobic stability (P < 0.01) and lower number of yeast (P < 0.01) in comparison to non-inoculated and did not differ between both inoculated (P > 0.01). Treated supplements had higher aerobic stability and lower yeast and mold counts than control supplement and did not differ between them. In experiment 2, 70% of dry rolled corn was substituted to reconstituted corn grain silage. Cattle consuming reconstituted corn grain silage supplement until 6 days of aerobic exposure had higher average daily gain and final body weight (P ≤ 0.06) tended to consume less supplement (P ≤ 0.09) and were more efficient in putting weight per kg of dry matter ingested (P ≤ 0.04). Aerobic exposition had no linear effect and did not impact cattle performance in comparison to fresh supplement. Inoculation with L. buchneri + L. hilgardii or L. buchneri + L. plantarum guarantee aerobic stability for 9 days in silage and for 6 days in supplement under laboratory conditions. Cattle consuming reconstituted corn grain silage supplement exposed until 6 days had better performance than cattle consuming dry corn supplement.